2007
DOI: 10.1037/0278-7393.33.6.983
|View full text |Cite
|
Sign up to set email alerts
|

From poor performance to success under stress: Working memory, strategy selection, and mathematical problem solving under pressure.

Abstract: Two experiments demonstrate how individual differences in working memory (WM) impact the strategies used to solve complex math problems and how consequential testing situations alter strategy use. In Experiment 1, individuals performed multistep math problems under low- or high-pressure conditions and reported their problem-solving strategies. Under low-pressure conditions, the higher individuals' WM, the more likely they were to use computationally demanding algorithms (vs. simpler shortcuts) to solve the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
305
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(343 citation statements)
references
References 78 publications
33
305
5
Order By: Relevance
“…Attempting to control solution progress via analytic or incremental approaches could also make the consideration of remote associations or novel solutions unlikely. Consistent with this hypothesis, studies have found that solvers with less working memory capacity, who possess less of an ability to control their own attention, can actually be more flexible creative problem solvers than participants with superior executive functioning (Ansburg & Hill, 2003;Beilock & DeCaro, 2007;Kim, Hasher, & Zacks, 2007). Similarly, creative problem solving performance seems to benefit when solvers are put in contexts that disrupt their ability to engage in more focused or controlled processing.…”
Section: Introductionsupporting
confidence: 50%
“…Attempting to control solution progress via analytic or incremental approaches could also make the consideration of remote associations or novel solutions unlikely. Consistent with this hypothesis, studies have found that solvers with less working memory capacity, who possess less of an ability to control their own attention, can actually be more flexible creative problem solvers than participants with superior executive functioning (Ansburg & Hill, 2003;Beilock & DeCaro, 2007;Kim, Hasher, & Zacks, 2007). Similarly, creative problem solving performance seems to benefit when solvers are put in contexts that disrupt their ability to engage in more focused or controlled processing.…”
Section: Introductionsupporting
confidence: 50%
“…The aforementioned researchers have suggested that when we are at our most flexible, we are actually not as prepared to perform a practiced task or primed response, which may help explain some cases of choking under pressure (e.g., Baumeister, 1984;Beilock & DeCaro, 2007). We can become more capable of taking multiple courses of (Experiments 1-3) and priming/color-switch cost (Experiments 4 and 5) when the reward increased from low to high, as compared with when the reward remained low.…”
Section: Discussionmentioning
confidence: 99%
“…Strategy selection as a function of working memory (differences in kind) WM capacity is indicative of the types of strategies chosen by individuals for some tasks (Beilock & DeCaro, 2007) and contributes to the explanation of individuals' strategy choices for our retrieval task. When participants were not under load, HWMs selected the most effective retrieval strategy (classification) more often than LWMs did.…”
Section: Productivity Of Specific Retrieval Strategiesmentioning
confidence: 99%